The effect of health promotion about breast self-examination for student’s knowledge at the first senior high school of Enam Lingkung Padang Pariaman - Herman, Hermalinda; H., Novriani; Putri, Yuyu E. (International Journal of Research in Medical Sciences, 2017)
Background: Breast self-examination (BSE) is one of the interventions to detect the breast cancer earlier. Nowadays, BSE didn’t known by the many adolescent and young women, so that it is needed to do promotive effort to increase their knowledge about BSE. The objective of this study was to determine the effect of health promotion about breast self-examination for Student’s knowledge at the first senior high school of Enam Lingkung Padang Pariaman. Methods: The research design was pre experimental with one-group pre-posttest design approach and was conducted on July 2014. The samples were students in tenth and eleventh class, which was taken by simple random sampling technique and the number of samples, were 75 people. Results: The survey results revealed an average score of knowledge before the intervention was (59.33) with a standard deviation (12.284), and average knowledge score after the intervention was (88.40) with standard deviation (7.220). The difference of the average scores of knowledge before and after the intervention was (29.067). The statistic test indicated that there was a difference of average score of knowledge before and after intervention with p value was (0.000). Conclusions: It can be expected for health professional to increase prevention efforts of breast cancer through health promotion about BSE in the school and community.